Endoscopic clearance of non‐complex biliary stones using fluoroscopy‐free direct solitary cholangioscopy: Initial multicenter experience - Wiriyaporn Ridtitid; Rungsun Rerknimitr; Mohan Ramchandani; Sundeep Lakhtakia; Raj J Shah; Janak N Shah; Nirav Thosani; Mahesh K Goenka; Guido Costamagna; Mihir S Wagh; Vincenzo Perri; Joyce Peetermans; et al. (DEN Open)
Abstract Background and Aims Fluoroscopy‐free endoscopic retrograde cholangiopancreatography for common bile duct stone (CBDS) clearance is usually offered only to pregnant patients. We initiated a multicenter, randomized controlled trial comparing clearance of non‐complex CBDSs using fluoroscopy‐free direct solitary cholangioscopy (DSC) to standard endoscopic retrograde cholangiography (ERC) to evaluate the wider applicability of the DSC‐based approach. Here we report the initial results of stone clearance and safety in roll‐in cases for the randomized controlled trial. Methods Twelve expert endoscopists at tertiary care centers in four countries prospectively enrolled 47 patients with non‐complex CBDSs for DSC‐assisted CBDS removal in an index procedure including fluoroscopy‐free cannulation. Successful CBDS clearance was first determined by DSC and subsequently validated by final occlusion cholangiogram as the ERC gold standard. Results Fully fluoroscopy‐free cannulation was successful in 42/47 (89.4%) patients. Brief fluoroscopy with minimal contrast injection was used in 4/47 (8.5%) patients during cannulation. Cannulation failed in 1/47 (2.1%) patients. Fluoroscopy‐free complete stone clearance was reached in 38/46 (82.6%) cases. Residual stones were detected in the validation ERC occlusion cholangiogram in three cases. Overall serious adverse event rate was 2.1% (95% confidence interval 0.1–11.3): postprocedural pancreatitis in one patient. Conclusions In patients with non‐complex CBDS, the fluoroscopy‐free technique is easily transferred to endoscopic retrograde cholangiopancreatography experts with acceptable rates of cannulation and stone clearance and few serious adverse events. (ClinicalTrials.gov number, NCT03421340)